2018
DOI: 10.5144/0256-4947.2018.1
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in mortality among ST elevation myocardial infarction patients in Malaysia from 2006 to 2013

Abstract: BACKGROUNDCoronary artery disease (CAD) is one of the leading causes of death in Malaysia. However, the prevalence of CAD in males is higher than in females and mortality rates are also different between the two genders. This suggest that risk factors associated with mortality between males and females are different, so we compared the clinical characteristics and outcome between male and female STEMI patients.OBJECTIVESTo identify the risk factors associated with mortality for each gender and compare differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…Understanding social barriers for female patients to seek emergent medical treatment after STEMI in a low income setting would be crucial in regard to improving clinical outcomes of female patients. Sex was not independently associated with increased in-hospital mortality in our study (Table 3), presumably due to small sample size and other confounding variables, while one study showed that the mortality rate of female patients after STEMI was two times higher than male counterparts [18]. More clinical and socioeconomic differences in female patients with STEMI should be scrutinized particularly in a low income setting in Bangladesh.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Understanding social barriers for female patients to seek emergent medical treatment after STEMI in a low income setting would be crucial in regard to improving clinical outcomes of female patients. Sex was not independently associated with increased in-hospital mortality in our study (Table 3), presumably due to small sample size and other confounding variables, while one study showed that the mortality rate of female patients after STEMI was two times higher than male counterparts [18]. More clinical and socioeconomic differences in female patients with STEMI should be scrutinized particularly in a low income setting in Bangladesh.…”
Section: Discussionmentioning
confidence: 55%
“…It is known that women are more prone to presenting with atypical symptoms (fatigue, dyspnea, nausea, and abdominal complaints) during STEMI and more likely to have the delay in seeking medical care. Moreover, several studies showed that there were differences in terms of clinical presentation, applying evidence-based therapies and clinical outcomes according to gender [[16], [17], [18]]. Understanding social barriers for female patients to seek emergent medical treatment after STEMI in a low income setting would be crucial in regard to improving clinical outcomes of female patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sigara kullanan bireylerde KAH başta olmak üzere bir çok kronik hastalık görülmektedir. Literatürde sigara kullanımı erkeklerde daha fazla olduğu bilinmekle birlikte [4,20] , özellikle son yıllarda sigara kullanımında kadın ve erkekler arasında fark olmadığını gösteren çalışma sonuçları da bulunmaktadır. [21,22] Bu araştırmada erkeklerde sigara kullanımı istatistiksel olarak yüksek bulundu.…”
Section: Cinsiyetunclassified
“…Various studies have found female gender to be associated with a significant increased risk of shortand long-term mortality after acute coronary event. [4][5][6][7][8][9][10][11][12][13] Nonetheless, there exist a conflict of evidence as ample literature also available suggesting either no gender differences in outcomes or attributing differences in outcomes with differences in baseline characteristics or increased burden of comorbidities in women due to relatively older age at presentation. 14,15 Studies reporting gender disparities in outcomes postulated various determinants of higher rate of adverse events in women, some studies argued that the atypical clinical presentation is more common among women also pre-hospital delay is more common for females as compared to their male counterpart resulting in delay in reperfusion therapy.…”
Section: Introductionmentioning
confidence: 99%